Enhancing Stakeholders’ Participation (Co-Management) Towards Achieving Ecosystem-Based Fisheries Management in The Nigerian Coastal Fisheries - Editor, Njred; Agbeja, Yetunde E. (The Nigerian Journal of Rural Extension and Development, 2023)
This paper highlights the importance of ecosystem-based fisheries management, importance of participatory fisheries management and discusses opportunities for the enhancement of participatory management towards achieving ecosystem-based fisheries management in the Nigerian coastal fisheries. The desire to move towards Ecosystem-Based Fisheries Management (EBFM) has been a common theme in fisheries policy and management discourse worldwide. Ecosystem Based Management (EBM) is a form of natural resource management that has grown consistently over the last two decades. It has emerged from the widespread feeling that traditional types of natural resource management have failed and that a new, more holistic way of understanding how ecosystems work is needed. Co-management systems have emerged over the years as a partnership arrangement using the capacities and interests of local resource users and complemented by the ability of government to provide enabling legislation, enforcement and conflict resolution mechanisms. The Nigerian coastal environment consists of rich and diverse ecosystems, natural resources and large human populations. Fishing is a major activity especially in the coastal areas where important resources such as fish, shellfish, such as shrimps, lobsters, crabs and molluscs are obtained. Successful implementation of Ecosystem approach to fisheries management will be highly beneficial to the economy and social well-being of the nation.